Mitochondrial hyperfusion causes neuropathy in a fly model of CMT2A. (20th July 2018) - Ueda, Eri; Ishihara, Naotada
Abstract : Mitochondria undergo frequent fusion and fission events, which are essential to maintain a functional mitochondrial network. A disruption of these processes can cause severe neurodegeneration. Charcot–Marie–Tooth disease type 2A (CMT2A) is a neuropathy that is caused by mutations in the fusion factor Mfn2. It is generally assumed that impaired mitochondrial fusion causes CMT2A. However, the detailed molecular mechanism underlying the pathophysiology of CMT2A is only incompletely understood. In this issue of EMBO Reports, El Fissi et al established a fly model to analyze the consequence of frequently occurring MFN2 mutations on locomotor behavior, mitochondrial morphology, and function and find that some pathogenic mutants enhance fusion activity, indicating that increased mitochondrial fusion can drive CMT2A‐like pathology1 . Moreover, this novel assay system will be a useful tool to analyze CMT2A pathogenesis in vivo . Abstract : Charcot‐Marie‐Tooth neuropathy type 2A is thought to be caused by impaired mitochondrial fusion. A study in this issue now establishes a fly model to show that mainly increased mitochondrial fusion drives CMT2A.